KLU/CYP78A5, a Cytochrome P450 Monooxygenase Identified via Fox Hunting, Contributes to Cuticle Biosynthesis and Improves Various Abiotic Stress Tolerances - Kajino, Takuma; Yamaguchi, Masahiro; Oshima, Yoshimi; Nakamura, Akiyoshi; Narushima, Jumpei; Yaguchi, Yukio; Yotsui, Izumi; Sakata, Yoichi; Taji, Teruaki (Frontiers in Plant Science, 2022)
Acquired osmotolerance after salt stress is widespread among Arabidopsis thaliana (Arabidopsis) accessions. Most salt-tolerant accessions exhibit acquired osmotolerance, whereas Col-0 does not. To identify genes that can confer acquired osmotolerance to Col-0 plants, we performed full-length cDNA overexpression (FOX) hunting using full-length cDNAs of halophyte Eutrema salsugineum, a close relative of Arabidopsis. We identified EsCYP78A5 as a gene that can confer acquired osmotolerance to Col-0 wild-type (WT) plants. EsCYP78A5 encodes a cytochrome P450 monooxygenase and the Arabidopsis ortholog is known as KLU. We also demonstrated that transgenic Col-0 plants overexpressing AtKLU (AtKLUox) exhibited acquired osmotolerance. Interestingly, KLU overexpression improved not only acquired osmotolerance but also osmo-shock, salt-shock, oxidative, and heat-stress tolerances. Under normal conditions, the AtKLUox plants showed growth retardation with shiny green leaves. The AtKLUox plants also accumulated higher anthocyanin levels and developed denser cuticular wax than WT plants. Compared to WT plants, the AtKLUox plants accumulated significantly higher levels of cutin monomers and very-long-chain fatty acids (VLCFAs), which play an important role in development of cuticular wax and membrane lipids. Endoplasmic reticulum (ER) stress induced by osmotic or heat stress was reduced in AtKLUox plants compared to WT plants. These findings suggest that KLU is involved in the cuticle biosynthesis, accumulation of cuticular wax, and reduction of ER stress induced by abiotic stresses, leading to the observed abiotic stress tolerances.